PSYCHOLOGICAL BARRIERS IN THE PROCESS OF LEARNING A FOREIGN LANGUAGE (Konferensiyalar | Conferences, 2024)
It is obvious to everybody that learning a language is challenging process, without having obstacles a person cannot achieve success in the field of a language, and the most crucial one is a psychological hurdle. This article discusses various types of psychological barriers in the process of learning a foreign language. It outlines the factors contributing to the emergence of this phenomenon, as well as describes possible technologies and methods for overcoming psychological barriers in the process of learning a foreign language.